TELAAH KRITIS PENERAPAN MANAJEMEN SUMBER DAYA INSANI PADA PERUSAHAAN (Studi Empiris Pada PT. Bank Muamalat Indonesia, Tbk. Cabang Bengkulu - Wahyuni, Eka Sri (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2017)
This study examines the implementation of human resource management in the company,by conducting an empirical study at PT. Bank Muamalat Indonesia, Tbk. Branch of Bengkulu. With so many companies today where the management system in its human resources aspects to implement the system of management with the principles of sharia.In these circumstances, researchers conduct critical reviews of human resource management systems in sharia-based companies. The purpose of this study is to represent the human resource management system in accordance with the perspective of shariah management.The type of research in this study is descriptive evaluative, by comparing the theory with empirical facts.The results of the study concluded that the implementation of human resource management at PT. Bank Muamalat Indonesia, Tbk Bengkulu Branch, for the process of Recruitment, Selection, and Performance Assessment is in accordance with the concept of sharia.While in the process of Training and Development, according to this author has not approached with the concept of sharia, because it is still lack of material balance, that is between material of Tauhid (Akhlak), Sharia, and Muamalah which is delivered to the employees when done Training.